2012
DOI: 10.1364/oe.20.012658
|View full text |Cite
|
Sign up to set email alerts
|

Broad combined orange-red emissions from Eu^2+- and Eu^3+-doped low-silica calcium aluminosilicate glass

Abstract: In this paper, a broad combined orange-red emission from Eu²⁺- and Eu³⁺-doped low-silica calcium aluminosilicate (LSCAS) glass is reported. Spectroscopic results demonstrate that it is possible to tune the emission wavelength by changing the excitation wavelength in the UV-Vis region. The color coordinates for the emission spectra were calculated, and using the Commission Internationale de l'Éclairage 1931 and 1976 chromatic diagrams, it is possible to note that they are dependent on the excitation wavelength.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…This behavior was in agreement with the ESR data. The coexistence of Eu 2þ and Eu 3þ in OH À -free LSCAS glass has been reported previously [10,11,29]. In an earlier study [29], overlapping of the emission lines between 570 and 750 nm was observed, attributed to the 5 D 0 / 7 F J (J 0, 1, 2, 3, and 4) transitions of the Eu 3þ ion.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…This behavior was in agreement with the ESR data. The coexistence of Eu 2þ and Eu 3þ in OH À -free LSCAS glass has been reported previously [10,11,29]. In an earlier study [29], overlapping of the emission lines between 570 and 750 nm was observed, attributed to the 5 D 0 / 7 F J (J 0, 1, 2, 3, and 4) transitions of the Eu 3þ ion.…”
Section: Resultssupporting
confidence: 71%
“…The observed behavior was like a mirror, compared to the ESR intensity. Although the use of 350 nm does not directly excite Eu 3þ , energy transfer from Eu 2þ to Eu 3þ by reabsorption is possible, due to the overlap among Eu 2þ absorption bands and Eu 3þ absorption lines, as reported recently [10]. Wang et al [30] suggested that a decrease in the Eu 2þ emission intensity can result from an increase in the number of non-bridging oxygens (NBOs), caused by a greater number of negative charges in the glass network.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…It is noteworthy that the quite broad and white emission spectrum obtained for the SiAlON:Eu films has been achieved with an almost uniform composition throughout the film (see Figure ). In contrast, other authors in order to achieve a similar white response have had to overlap the contribution of films or powders with different compositions, each with a narrow emission in order to obtain similar chromatic coordinates . Therefore these results are relevant because they show that amorphous SiAlON films with a nanostructured Eu 2+ ‐doping might be used for solid state white‐light emitters such as field emission flat lamps and displays.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the potentiality of low silica calcium aluminosilicate (LSCAS) glass to generate smart lighting was studied in Eu 3 þ /Eu 2 þ doped samples [14] and the results showed that Eu 2 þ yelloworange emission can be combined with Eu 3 þ red emission for white light phosphor. Over the past, we have studied Eu 2 þ doped calcium aluminosilicate (CAS) glass [15] and showed that this material is a promising phosphor toward the development of a smart lighting.…”
Section: Introductionmentioning
confidence: 99%